Simple modeling of infrared drying of fresh apple slices - Togrul, H (Elsevier Sci Ltd, 2005)
The effect of drying temperature on drying rates of apple slice was examined at different temperature. The values of drying rate almost doubled when the drying temperature was increased from 50 to 80 C. The experimental drying data were applied to various drying equation (Newton, Page, Modified Page, Wang and Singh, Henderson and Pabis, Logarithmic, Diffusion approach, Simlified Fick's diffusion SFFD equation, Modified Page equation-II and Midilli equation). Midilli equation was best for characterizing drying behavior of apple for the whole range of temperature. The variation of these models parameters with temperature were described as Arrhenius and logarithmic type function of drying temperature. Sixty-six different model equations that describing the temperature and time dependence of infrared drying of apple were derived. Theoretical models describing temperature and time dependence of drying were fitted to experimental data and model parameters in equations were determined by multiple regression analysis in temperature range 50-80 degrees C. Model 50 derived from Modifiye Page II has lowest RMSE, MBE and chi-square and the highest modeling efficiency and regression coefficient. The moisture ratio change during infrared drying (0-240 min) of apple in the temperature range of 50-80 degrees C can be predicted by single equation: MR = exp (-(-9.08244 + 1.580765 In(T))(t/(-0.628792 + 0.574354 In(T))(2))((11.49544-1.740161In (T)))). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: apple; infrared drying; mathematical model; statistical test